Analysis of management decisions and outcomes of a weekly multidisciplinary pediatric tumor board meeting in Uganda - Paul E George; Geriga Fahdil; Israel Luutu; Alfred Bulamu; John Sekabira; Nasser Kakembo; Susan Nabadda; Sam Kalungi; Joyce B Kambugu (Future Science OA, 2019)
Aim: To evaluate the efficacy of a pediatric multidisciplinary tumor board (MTB) in Uganda. Patients & methods: We documented the discussion of cases presented at a pediatric MTB and subsequently, though retrospective chart review, determined the degree to which decision were implemented. Results: 95 patients were discussed. In total, 129 of 226 (57%) distinct management decisions reached during the MTBs were implemented. Of these, 15 resulted in changes in diagnosis and 53 were classified as major changes in management. Decisions on chemotherapy were the most likely to be successfully enacted (51/58), followed by radiotherapy (18/30) and surgery (12/21). Labs/consults were less likely to be implemented. Conclusion: Key improvements, specifically in the documentation and implementation of management decisions, are needed to improve the MTB’s efficacy.